The Usage of Virtual Local Area Networks to Address Cybercrime - Bandr Siraj Fakiha (International Journal of Advanced Science and Technology, 2020)
The use of the internet is amongst the fastest growing areas of technical infrastructural development in the global information cyberspace. Like corporations elsewhere around the world, business organizations are increasingly facing cyber-attacks arising from their internet connectivity. Consequent upon this evolving internet security challenge, it is imperative to explore the various measures that organizations can take to provide a trustworthy and effective operational environment free from cyber-attack. The capstone project has utilized cross-sectional design in investigating the extent to which Virtual Local Area Networks (VLANs) can be applied to address the cybercrime challenges faced by organizations. In doing that, a three department simulation company had their single network system separated into three different domains: VLAN 100, VLAN 200, and VLAN 300, for the finance, administration and production departments respectively. All the switches for the three departments were separated. In doing the setting for this design, every single interface was actually configured into the individual VLAN. The three networks, in this case, did not share the main broadcast domain but instead had their individual sub-domains. This experiment aimed to determine if such separation could assist in trying to enhance the overall efficiency as well as the functionality of the whole network system of the company. Segmentation of network in the virtual local area networks (VLANs) produced a larger amount of networks that were isolated within the whole data centre. This would prevent severe access to the surface for system attack. It also helped minimize the packet-sniffing abilities and reduced the effort of a threat agent. The present research has concluded that decentralization of the company's network system by configuring VLANs can improve the internet security of a given company.